Geomechanical modeling of fault-propagation folds: A comparative analysis of finite-element and the trishear kinematic model - Plotek, Berenice Lia (2024)
Fault-propagation folds are common structures within fold and thrust belts. The trishear kinematic model has been widely used to understand the kinematics and geometry of these folds, effectively reproducing various characteristics. However, the resulting geometry of natural prototypes may diverge from the predictions of the trishear model depending on the rheological properties involved in the deformation. In order to address this limitation, finite element viscoplastic numerical models were implemented. The analysis revealed that in models with a 15° fault angle, these simulations develop a mechanically weaker discontinuity, which is defined as the low viscosity zone (LVZ). The LVZ induces faulting and absorbs slip, causing deviations of velocity vectors from parallel alignment with the main reverse ramp. In models with fault angles set at 25° or 35°, the kinematic vectors of the hanging wall aligned parallel to the ramp, and a zone of progressive rotation of the velocity vectors was observed in the forelimb, resembling the theoretical trishear zone. In these scenarios, the resulting folds exhibited greater symmetry. However, in cover layers with a viscosity equal to 1020 Pa s, the forelimb exhibits the highest velocities, which is attributed to material flow toward the footwall.